2020
DOI: 10.1101/2020.09.11.292870
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Striatal BOLD and midfrontal theta power express motivation for action

Abstract: Action selection is biased by the valence of anticipated outcomes. To assess the mechanisms by which these motivational biases are expressed and controlled, we measured simultaneous EEG-fMRI during a motivational Go/NoGo learning task (N=36), leveraging the temporal resolution of EEG and subcortical access of fMRI. VmPFC BOLD encoded cue valence, importantly predicting trial-by-trial valence-driven response speed differences and EEG theta power around cue onset. In contrast, striatal BOLD encoded selection of … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 7 publications
(19 citation statements)
references
References 131 publications
(247 reference statements)
4
15
0
Order By: Relevance
“…This idea is supported by a recent study in marmoset monkeys by Duan et al (2021) 65 showing that the rostral anterior cingulate cortex is necessary for detecting instrumental control of actions over outcomes, while the anterior orbitofrontal cortex (OFC) mediates Pavlovian influences on goal-directed behaviour. In line with this we have also recently shown that BOLD activity in the orbitofrontal / ventromedial prefrontal cortex predicts the degree of valence-induced invigoration 66 . This notion would align with previous work showing that modulating frontal dopamine can reconfigure connectivity patterns between OFC and other brain regions suggesting a key role in shaping functional brain circuitry 67 .…”
Section: Discussionsupporting
confidence: 83%
“…This idea is supported by a recent study in marmoset monkeys by Duan et al (2021) 65 showing that the rostral anterior cingulate cortex is necessary for detecting instrumental control of actions over outcomes, while the anterior orbitofrontal cortex (OFC) mediates Pavlovian influences on goal-directed behaviour. In line with this we have also recently shown that BOLD activity in the orbitofrontal / ventromedial prefrontal cortex predicts the degree of valence-induced invigoration 66 . This notion would align with previous work showing that modulating frontal dopamine can reconfigure connectivity patterns between OFC and other brain regions suggesting a key role in shaping functional brain circuitry 67 .…”
Section: Discussionsupporting
confidence: 83%
“…For combined EEG-fMRI analyses, we excluded the abovementioned six participants plus one more participant whose regression weights for every regressor were about ten times larger than for other participants, leaving 29 participants (M age = 23.00, 22 women). Exclusions were in line with a previous analysis of this data set (32). fMRI-and EEG-only results held when analyzing only those 29 participants (see S01).…”
Section: Participantssupporting
confidence: 84%
“…These filter settings allowed us to distinguish the delta, theta, alpha, and beta band, while filtering out residual high-frequency MR noise. This low-pass filter cut-off was different from a previous analysis of this data in which we set it at 15 Hz (32) because in this analysis, we had a hypothesis on outcome valence encoding in the beta range. We then applied linear baseline correction based on the 200 ms prior to cue onset and used ICA to detect and reject independent components related to eye-blinks, saccades, head motion, and residual MR artifacts (mean number of rejected components per participant: 32.694, range .…”
Section: Eeg Pre-processingmentioning
confidence: 98%
See 2 more Smart Citations